Tubular ceramic membranes coated with ZnO and applied in the disinfection of water contaminated with Staphylococcus aureus. Issue 19 (1st October 2021) - da Silva Biron, Dionisio; Santos, Venina dos; Bergmann, Carlos Pérez
Abstract: In this study, commercial ceramic membranes of mullite and of alumina were coated with nanostructured ZnO using 3-aminopropyltriethoxysilane (APTES) as the connecting molecule between ceramic and ZnO. The characterization of ceramic membranes containing ZnO was performed by SEM, EDS and ICP-OES. The membranes without and with ZnO coating were applied in microfiltration tests to evaluate their antimicrobial capacity in the disinfection of distilled water contaminated with Staphylococcus aureus . In the microfiltration tests, ceramic membranes without the ZnO coating showed low efficiency in water disinfection, 35 and 45%, for mullite and alumina membranes, respectively. After the coating with nanostructured ZnO, both membranes showed disinfection efficiencies greater than 99%. The results obtained justify the application of ZnO as a promising coating on both mullite and alumina membranes for application in microfiltration aiming the disinfection of water contaminated with Staphylococcus aureus . Graphical abstract: Coating process of ceramic membranes with ZnO and its antimicrobial action. Image 1